Gut Microbiota Analysis in Postoperative Lynch Syndrome Patients - Mori, Giorgia; Orena, Beatrice Silvia; Cultrera, Ilenia; Barbieri, Giulia; Albertini, Alessandra M.; Ranzani, Guglielmina Nadia; Carnevali, Ileana; Tibiletti, Maria Grazia; Pasca, Maria Rosalia (Frontiers in Microbiology, 2019)
Lynch Syndrome (LS) is a dominantly inherited condition with incomplete penetrance, characterized by high predisposition to colorectal cancer (CRC), endometrial and ovarian cancers, as well as to other tumors. LS is associated with constitutive DNA mismatch repair (MMR) gene defects, and carriers of the same pathogenic variants can show great phenotypic heterogeneity in terms of cancer spectrum. In the last years, human gut microbiota got a foothold among risk factors responsible for the onset and evolution of sporadic CRC, but its possible involvement in the modulation of LS patients’ phenotype still needs to be investigated. In this pilot study, we performed 16S rRNA gene sequencing of bacterial DNA extracted from faecal samples of 10 postoperative LS female patients who had developed colonic lesions (L-CRC) or gynecological cancers (L-GC). Our preliminary data show no differences between microbial communities of L-CRC and L-GC patients, but they plant the seed of the possible existence of a faecal microbiota pattern associated with LS genetic background, with Faecalibacterium prausnitzii, Parabacteroides distasonis, Ruminococcus bromii, Bacteroides plebeius, Bacteroides fragilis and Bacteroides uniformis species being the most significantly over-represented in LS patients (comprising both L-CRC and L-GC groups) compared to healthy subjects.